Robotic Modified Orr-Loygue Rectopexy for Internal and External Rectal Prolapse - Arifa Siddika; Shahab Siddiqi (Annals of Robotics and Automation - Peertechz Publications, 2017)
Abstract Laparoscopic ventral mesh rectopexy is the gold standard treatment for external rectal prolapse and an excellent treatment for symptomatic internal rectal prolapse. However, there is a recurrence rate for this procedure, part of which can be attributed to the untreated posterior rectal prolapse component. Here we escribe a robotic Orr-Loygue rectopexy where an additional posterior mesh rectopexy is performed.This differs from other surgical descriptions in that the posterior mesh can be sutured to the rectal tube without risking rectal denervation, which would be a difficult proposition using a laparoscopic approach.